Design of an oil-immersed pulse modulator for X-band 50-MW klystron - Liu, Yong-Fang (2023)
This article presents a compact high-voltage pulse modulator used for a 50-MW X -band pulsed klystron (11.4 GHz) at Shanghai Advanced Research Institute, Chinese Academy of Sciences (SARI, CAS). The pulse modulator includes a ten-section pulse-forming network (PFN), protection circuits, a thyratron module, and a pulse transformer. To reduce the volume of the pulse modulator and maintain the system stability, an oil-immersed tank is proposed to insulate the main electronic components, which leads to a volume reduction of 65%. The modulator is designed with a peak pulse voltage of 427 kV, a peak pulse current of 304 A, a repetition rate of 50 Hz, and a flat-top pulsewidth of 1.3 μ s. The circuit schematic is provided, while the design criteria of the main components and mechanical structure are discussed. The experimental results and measurements show the design and hardware to be capable of fulfilling the requirements.